THE IMPORTANCE OF THE CORRECT APPLICATION OF VALUE ADDED TAX FROM THE ASPECT OF THE TAX DEBTOR FOR TURNOVER IN THE FIELD OF CONSTRUCTION - Djelkapić, Tanja (Glasnik Advokatske komore Vojvodine, 2022)
In today's form of social and economic organization, taxes are the basis of the public revenues in all countries and the dominant instrument for covering budget expenditures. Of all taxes, in the Republic of Serbia, the largest budget provider is the Value Added Tax. The aim of this paper is to show the importance of proper application of Value Added Tax in the structure of public revenues, and the importance of its proper calculation from the aspect of the tax debtor, as well as all the consequences arising from improper application of this Tax. In this regard, on the example of the VAT payer- tax debtor, within the construction activity, the correct and incorrect calculation of Value Added Tax will be shown and the consequences for the national budget and taxpayers who participate in that turnover will be analyzed.
Keywords: VAT; Tax debtor; Construction; tax; Republic of Serbia